Ovarian sarcoma a diagnostic dilemma- A case report - Prashant K Zulpi; Akshay B Kalavant; Anil B Halgeri; P Priyanka (Wolters Kluwer Medknow Publications, 2023)
Primary sarcoma of the ovary is extremely rare. There are inadequate data in the literature regarding ovarian sarcoma in the pediatric age group. We report a case of an 8-year-old girl presenting with large abdominal mass and cachexia. Raised alpha-fetoprotein levels suggested germ cell tumor. Tru-cut biopsy histopathological report suggested a spindle cell tumor. The IHC staining suggested non rhabdomyosarcoma. As tumour was large and ovarian pediatric non rhabdomyosarcoma was not reported in the literature, we started on rhabdomyosarcoma neoadjuant regimen. Good response was noted for neoadjuvant chemotherapy, which was followed by complete surgical excision of the tumor and radiotherapy. At present, the overall outcome of the disease is dismal. Increased available data and gaining more evidence may help in improvising the treatment option.